Disease Activity and Bone Mineral Density of MCP Joints in Patients with Rheumatoid and Psoriatic Arthritis: Is There a Correlation?—A Study in Patients Treated with Methotrexate and an Anti-TNFα Agent. (7th December 2013) - Bertoldi, Ilaria; Filippou, Georgios; Scirè, Carlo Alberto; Picerno, Valentina; di Sabatino, Valentina; Adinolfi, Antonella; Pierguidi, Serena; Galeazzi, Mauro; Frediani, Bruno
Abstract : Background . Bone damage in rheumatoid arthritis (RA) and in psoriatic arthritis (PsA) includes an accelerated bone mineral density (BMD) reduction. The objective was to evaluate BMD variations of the metacarpophalangeal joints (MCPs) in patients starting treatment with methotrexate (MTX) or etanercept. Methods . Patients affected by RA or PsA with hand joints involvement and with moderate or high disease activity, were enrolled in this study. All patients underwent clinical examination, laboratory exams, and a DXA scan of the most affected hand, as assessed with an ultrasound examination at the baseline, at the time of enrolment and after 1, 3, 6, and 12 months. Patients non-responders to MTX received combination therapy, while patients with no previous treatment initiated MTX. Results . 22 patients were enrolled. In both RA and PsA groups, BMD increased independently of the treatment. However, in the patients affected by RA, a slight BMD decrease was observed at the last checkup. Globally, the BMD variations of the MCPs were strongly correlated with the disease activity. At the reduction of DAS28, the scores corresponded an increase of BMD. Conclusions . MCPs BMD is inversely correlated to disease activity. BMD increase seems to be correlated with the response to treatment and not with the drug itself.